A Review on the Orthoplastic Approach to Lower Limb Reconstruction - Shaun D. Mendenhall; Oded Ben-Amotz; Rikesh A. Gandhi; L. Scott Levin (Indian Journal of Plastic Surgery, 2019)
Just as in the craft of carpentry, a stable foundation and framework are absolutely essential to the final function of a building, but no more important than the drywall, trim, and paint that make the building functional, durable, and livable. Reconstruction of the lower extremity is similar; the orthopaedic surgeon must obtain stable fixation of the damaged or diseased bone once a thorough debridement of nonviable bone is performed, while the plastic or orthopaedic soft tissue surgeon must provide vascularized, stable coverage. These two components are complementary and both contribute to the success or failure of functional limb restoration. The stability of bone repair will predict the ultimate functional status, while the vascularized envelope will enhance the biology of bone and soft tissue healing. When both components are properly attended to, the result is often a functional limb with an acceptable appearance. While a single surgeon need not perform both of these tasks (although some may choose to do so), the orthopaedic and plastic surgeon involved in this care must have a clear understanding of each other's role and their importance for a good outcome. This is what we call the orthoplastic approach to reconstructive surgery of the extremities, that is, the application of principles and practice of both specialties applied simultaneously to optimize the outcomes in limb reconstruction. In this review article, we discuss the history of orthoplastic surgery, the key elements of orthoplastic surgery, and thoughts on factors that lead to good outcomes through select cases.